A new system of indicators for European development policy? - Ulrike Winkelmann; Martin Gercke (European Regional Science Association (ERSA), 1998)
The first version of a European spatial development perspective (ESDP) approved by the informal conference of ministers for regional policy and planning in June 1997 includes a proposal for a new "system of indicators". The purpose of this system of indicators is to form the basis for a typology of European regions and for a set of scenarios on the future development of the European space. The need to improve the present standards of spatial analysis within the European Union is clearly demonstrated by the ESDP. Nevertheless, the indicators proposed in the document (geographical location, economic potential, social and spatial integration, land use intensity among others) represent only vague descriptions of spatial characteristics somehow relevant for regional development. Important questions still remain: How could these characteristics be defined in a feasible operational way? Which regional level is most appropriate for this kind of analysis? Is it at all possible to provide the required data for these spatial units? In general, European regional policy as actually applied in the context of the Structural Funds indicates quite different trends: the delineation of promotion areas, especially objective 2 areas and objective 5b areas, is partly based on qualitative criteria; as a consequence, the process of application for regional aid is open to interpretation of these criteria by national and regional governments. According to the principle of subsidiarity, this could be regarded as a positive factor of decision making. On the other hand, the number of promotion areas and programmes seems to expand beyond the EU's possibility to finance them. Therefore the reform of the Structural Funds will have to define new criteria capable of evaluating the need for EU assistance among European regions on a common basis, which must at the same time be able to reflect specific regional characteristics and development potential. The paper gives an overview of the need for and the framework of a new system of indicators.
Keywords: 330